2,5-Dihydroxyphenylethanone: an anti-melanogenic bioactive compound isolated from Ganoderma cochlear - Meng Ning; Xiao-Cui Liu; Min He; Xing-Rong Peng; Ming-Hua Qiu (Journal of Enzyme Inhibition and Medicinal Chemistry)
2,5-dihydroxyacetophenone, a natural product from the fruiting bodies of Ganoderma cochlear, can effectively and safely inhibit the production of melanin in zebrafish model. To achieve analogues with more significant inhibition, 9 analogs were synthesised and 13 analogues were purchased commercially. Among them, 14 compounds can inhibit melanin production, of which 5 compounds displayed the most significant inhibitory effects, with inhibitory rates of more than 80%, compared to positive control SymWhite®377 (phenylethyl resorcinol). This study elucidated the melanin-inhibitory effects of 2,5-dihydroxyacetophenone and its analogs, providing a theoretical foundation for their potential applications in anti-melanogenic reagents.